Memahami Makna Interaksi Sosial dalam Keanekaragaman Etnis dan Budaya di Kelurahan Subagan Karangasem pada Abad Ke-19 Perspektif Masa Kini - Mahyuni, Ida Ayu Putu; Inten Asmariati, Anak Agung (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p14, 2022)
Since the 19th century in Karangasem there has been interaction between various ethnic groups (Balinese, Sasak, Bugis, and Javanese). These social interactions lead to acculturation in several elements of culture, such as in elements of language, and cultural arts. The Sasak, Javanese, Bugis people migrated to Karangasem with various backgrounds and reasons, bringing with them their respective cultures. Gradually the cultural elements brought were accepted and processed into the Balinese Hindu culture, which is a native of Karangasem. Social interactions and acculturation that occur especially with Sasak Muslims cannot be separated from the existence of political power relations. Political power relations are also based on patron-client relationships, namely the relationship or link between the King of Karangasem as a leader and the people he leads. In the past, patron-client relationships were based on a sense of Utun (attention, loyalty), Tresna (loyalty and devotion (mutual respect and respect), mutual benefit, giving and receiving). Such leadership patterns are usually based on the teachings of Hindu philosophy, such as in the teachings of Asta Brata. This study is supported by the theory of structural functionalism, and the theory of hegemony from Gramsci. According to the theory of hegemony, mastering is not just dominating, but also with moral and intellectual leadership. The method used in this writing is through a literature review and the results of observations (observations).